STABILISASI BEKATUL DALAM UPAYA PEMANFAATANNYA SEBAGAI PANGAN FUNGSIONAL - Dewi, Ni Made Ayuk Puspita; Suter, I Ketut; Widarta, I Wayan Rai (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 1 No 1 (2012): Jurnal ITEPA, 2012)
Rice bran has a high fat content so prone to rancidity. Therefore, it is necessary to inactivate lipase stabilization process which is the cause of rancidity. Factors affecting the rice bran stabilization is temperature and time. Appropriate stabilization method can minimize the damage as well as bioactive components of rice bran lipase inactivate simultaneously. Bran stabilization at low temperature (100 ° C) within a longer time (15 min) was able to inactivate lipase contained in the bran and maintain the composition of bioactive components and antioxidant activity of rice bran
Keywords: stabilization of rice bran, bioactive compounds, functional food